Effect of N‐Acetyltransferase 2 Genotype on the Pharmacokinetics of Hydralazine During Pregnancy. (30th June 2019) - Han, Lyrialle W.; Ryu, Rachel J.; Cusumano, Michael; Easterling, Thomas R.; Phillips, Brian R.; Risler, Linda J.; Shen, Danny D.; Hebert, Mary F.
Abstract: Hydralazine, an antihypertensive agent used during pregnancy, undergoes N ‐acetylation primarily via N ‐acetyltransferase 2 (NAT2) to form 3‐methyl‐1, 2, 4‐triazolo[3, 4‐a]phthalazine (MTP). To characterize the steady‐state pharmacokinetics (PK) of hydralazine during pregnancy and evaluate the effects of NAT2 genotype on hydralazine and MTP PK during pregnancy, 12 pregnant subjects received oral hydralazine (5‐25 mg every 6 hours) in mid‐ (n = 5) and/or late pregnancy (n = 8). Serial blood samples were collected over 1 dosing interval, and steady‐state noncompartmental PK parameters were estimated. Subjects were classified as either (rapid acetylators, n = 6) or slow acetylators (SAs, n = 6) based on NAT2 genotype. During pregnancy, when compared with the SA group, the RA group had faster weight‐adjusted hydralazine apparent oral clearance (70.0 ± 13.6 vs 20.1 ± 6.9 L/h, P <  .05), lower dose‐normalized area under the concentration‐time curve (AUC; 1.5 ± 0.8 vs 5.9 ± 3.7 ng·h/mL, P <  .05), lower dose‐normalized peak concentrations (0.77 ± 0.51 vs 4.04 ± 3.18 ng/mL, P <  .05), and larger weight‐adjusted apparent oral volume of distribution (302 ± 112 vs 116 ± 45 L/kg, P <  .05). Furthermore, the MTP/hydralazine AUC ratio was ∼10‐fold higher in the RA group (78 ± 30 vs 8 ± 3, P <  .05) than in the SA group. No gestational age or dose‐dependent effects were observed, possibly because of the small sample size. This study describes for the first time, the PK of oral hydralazine and its metabolite, MTP, during pregnancy, and confirmed that the PK of oral hydralazine is NAT2 genotype dependent during pregnancy.